Management of Intellectual Property in The Light of Jurisprudence - Jacek OTTO; Izabela URBANIAK-MASTALERZ (Communications of International Proceedings, 2021)
The study presents the issues of managing intellectual property protection in the light of both Polish and EU jurisprudence. The article indicates the selected emerging problems related to the effective management of intellectual property based on court decisions in the field of understanding a work and a trademark. The authors will attempt to resolve the problem of how to interpret the issue of managing the protection of intellectual property in the context of the jurisprudence of various courts in this matter. Conclusions made on the basis of the considered judgments along with the available statistics will constitute a starting point for the assessment and capabilities of intellectual property managers.
Keywords: Management; Intellectual Property; Jurisprudence; Protection; Assumptions